Inpatient Program Instills Hope and Provides Patient-Centered Care - Buckley, Rita (MD Conference Express, 2015)
Although recovery is integral to psychiatric mental health (PMH) nursing, inpatient care is still rooted in the medical model’an approach that charges nurses with patient safety and maintaining control of the unit. This article discusses a program that teaches PMH nurses how to embrace recovery principles, instill hope, provide patient-centered care, and pave the way for healing.